Designing and optimizing carbon nanotube field effect transistor using taguchi method and the circuit performance analysis / Muhammad Faris Abdul Hadi - Abdul Hadi, Muhammad Faris (2024)
The 2022 IRDS emphasized CNTFET as a CMOS replacement. Thus, further optimizing the CNTFET physical parameter is a must to provide a better performance in circuit application. However, changing physical parameters might involve trade-offs between performance and reliability of the CNTFET. For instance, while reducing the diameter of Carbon Nanotube (CNT) might reduce power consumption of the applied circuit, but the changes could simultaneously compromise its propagation delay. Balancing these trade-offs to achieve both high performance and reduce reliability is a critical challenge.